The "Anthropocene": neglects, misconceptions, and possible futures: The term "Anthropocene" is often erroneously used, as it is not formally defined yet. (16th June 2017) - Rull, Valentí
Abstract : Despite its popularity in scientific and social media, the "Anthropocene" is a term and concept still under discussion and still not formally recognized as a new geologic epoch.